Surgical Treatment Results of Foot Deformities in Artrogryposis - Karakurt, Lokman; Varol, Tahir (Fırat University, 2007)
Objectives: We evaluated the clinical results of surgical treatment for foot deformities in patients with arthrogryposis. Material and Methods: There were rigid type clubfoot deformity in 8 feet of 4 cases and calcaneovarus deformity in 2 feet of 1 case. We performed complete subtalar release in all of 8 feet with clubfoot deformity. We added lateral column shortening in only 1 foot. We performed extansör tendon lengthening before complete subtalar release in 2 feet with calcaneovarus deformity. Results: Skin necrosis developed in 3 feet. Two of them responded conservative treatment. We used fasciocutaneous flap after debridement for other foot. In one patient, the additional surgical procedures included lateral column shortening and a second complet subtalar release for one side and lateral column shortening for other side. We obtained good results in 6 feet, excellent results in 4 feet.. Conclusion: Deformity recurrence is common. By a well planned surgery and a surgeon with experience, successful results can be obtained. ©2007, Firat University, Medical Faculty

Giriş: Artrogripozisli hastalardaki ayak deformitelerine uyguladığımız cerrahi tedavi yöntemlerini ve sonuçlarımızı tartışmayı amaçladık. Gereç ve Yöntem: 5 olgunun (4 erkek, 1 kız) 4'ünde (8 ayak) rijit tip clubfoot deformitesi, 1' inde (2 ayak) pes kalkaneovarus deformitesi vardı. Clubfoot deformiteli 8 ayağın tümüne komplet subtalar gevşetme yapıldı. Bir ayakta, komplet subtalar gevşetmeye lateral kolon kısaltması eklendi. Bilateral pes kalkaneovarus deformiteli olguya ise ekstansör tendon uzatmasını takiben bilateral komplet subtalar gevşetme yapıldı. Bulgular: Üç ayakta cilt nekrozu gelişti. Bunların 2'sinde konservatif tedavi ile nekroz iyileşti. Diğer ayakta ise nekrotik bölge debride edilip fasyakutanöz flep çevrildi. Bir hastanın bir ayağında komplet subtalar gevşetme tekrarlandı ve her iki ayağına lateral kolon kısaltması eklendi. Altı ayakta iyi, 4 ayakta mükemmel sonuç elde edildi. Sonuç: Artrogripoziste deformitenin rekürrensi sıktır. Ancak, iyi programlanmış bir cerrahi ve tecrübeli bir cerrah ile başarılı sonuçlar elde edilebilir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Artrogripotik Ayak Deformitelerinde Cerrahi Tedavi Sonuçlarımız